PENGARUH PENAMBAHAN EKSTRAK TEH HIJAU (Camellia sinensis) DALAM BAHAN PENGENCER SUSU SKIM KUNING TELUR TERHADAP KUALITAS SPERMATOZOA DOMBA SAPUDI YANG DISIMPAN PADA SUHU DINGIN - Swari, Wahyu Retno; Sabdoningrum, Emy Koestanti; Wurlina, Wurlina; Susilowati, Suherni; Kurnijasanti, Rochmah; Safitri, Erma (Ovozoa: Journal of Animal Reproduction, 2019)
The purpose of this study was to determinated the effect and the best concentration of greentea extract in skim milk and egg yolk diluent for quality sapudi sheep spermatozoa were measured in motility, viability and intact plasma membrane that was stored on cold temperature. The semen was devided into four groups; skim milk and egg yolk diluent, 0,5% green tea extract in skim milk and egg yolk diluent, 0,1% green tea extract in skim milk and egg yolk diluent, and 0,15% green tea extract in skim milk and egg yolk diluent. Spermatozoa quality was observed day 1, day 2, day 3, day 4 and day 5 after being diluted. The data obtained was analyzed with the Analysis of Variant (ANOVA), followed by multiple range test duncan. The results showed that the highest percentage of motility, viability and intact plasma membrane derived from green tea extract 0,15% on skim milk and egg yolk diluent  for 1 day storage is 86.66b ± 2.58, 92.00b ± 1.78, and 74.16b ± 3.25. The lowest percentage of motility, viability and intact plasma membranes was obtained from the skim milk and egg yolk diluent for 5 days storage is 43.33a ± 6.05, 56.50a ± 3.08 and 28.33a ± 2.80. The conclusion of this study is the addition of 0.15% green tea extract in a skim milk and egg yolk diluent can maintain the quality of sperm for up to 5 days of storage at cold temperatures.